RIFM fragrance ingredient safety assessment, 2, 2, 3-trimethyl-3-cyclopentene-1-acetaldehyde, CAS Registry Number 4501-58-0. (May 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: 2, 2, 3-Trimethyl-3-cyclopentene-1-acetaldehyde; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.